Comparison of the consumption of antidepressants in the immigrant and native populations in a Spanish health region: an observational study - Cruz, Inés (BioMed Central, 2010)
BACKGROUND: Health professionals and organizations in developed countries adapt slowly to the increase of ethnically diverse populations attending health care centres. Several studies report that attention to immigrant mental health comes up with barriers in access, diagnosis and therapeutics, threatening equity. This study analyzes differences in exposure to antidepressant drugs between the immigrant and the native population of a Spanish health region. METHODS: Cross-sectional study of the dispensation of antidepressant drugs to the population aged 15 years or older attending the public primary health centres of a health region, 232,717 autochthonous and 33,361 immigrants, during 2008. Data were obtained from computerized medical records and pharmaceutical records of medications dispensed in pharmacies. Age, sex, country of origin, visits, date of entry in the regional health system, generic drugs and active ingredients were considered. Statistical analysis expressed the percentage of persons exposed to antidepressants stratified by age, gender, and country of origin and prevalence ratios of antidepressant exposition were calculated. RESULTS: Antidepressants were dispensed to 11% of native population and 2.6% of immigrants. Depending on age, native women were prescribed antidepressants between 1.9 and 2.7 times more than immigrant women, and native men 2.5 and 3.1 times more than their immigrant counterparts. Among immigrant females, the highest rate was found in the Latin Americans (6.6%) and the lowest in the sub-Saharans (1.4%). Among males, the highest use was also found in the Latin Americans (1.6%) and the lowest in the sub-Saharans (0.7%). The percentage of immigrants prescribed antidepressants increased significantly in relation to the number of years registered with the local health system. Significant differences were found for the new antidepressants, prescribed 8% more in the native population than in immigrants, both in men and in women. CONCLUSIONS: All the immigrants, regardless of the country of origin, had lower antidepressant consumption than the native population of the same age and sex. Latin American women presented the highest levels of consumption, and the sub-Saharan men the lowest. The prescription profiles also differed, since immigrants consumed more generics and fewer recently commercialized active ingredients.